The Organizational Structure of the Arab Revolutionaries Movement - Iraq from October 1, 1966, to July 30, 1968 According to Secret Documents (A Documentary Study) - Dr. Manaf Chasib Mohammad Ali, (Thi Qar Arts Journal, 2025)
This research addresses the organizational structure of the Arab Revolutionaries Movement - in Iraq from its establishment on October 1, 1966, until its dissolution on July 30, 1968, during which its founders were completely removed from the political scene, and many were later eliminated for political purposes. Some secret statements from the movement were issued after this date until 1970.This political organizational movement was very secretive, especially after its dissolution on July 30, 1968. Before this date and at the beginning of its establishment, its activities were semi-public, as evidenced by its initial statements calling for the creation of a new revolutionary generation that believes in the principles of peaceful revolution and seeks to improve the political, economic, social, and cultural conditions in the country, fight colonialism, local bourgeoisie, feudalism, and reactionary forces. It also called for joining the Arab environment, declaring comprehensive Arab unity, and liberating Arab lands in Palestine. The movement initially praised the ruling regime at the time, considering it a purely nationalist rule and commending its efforts in this field. The movement's activities then became semi-secret, and it began to issue statements cautiously as it prepared to overthrow the ruling regime and take over power through a coup to correct the wrong path that things had taken.This movement played the primary and essential role in preparing, organizing, and executing the July 17, 1968 movement in Iraq. However, the Ba'ath Party sought to obscure and conceal its establishment, activities, and everything related to it. The Ba'athists, due to their weakness, initially sought to attract, appease, and win over the movement's leaders by giving them leadership positions in the government until they stabilized and then eliminated them on July 30, 1968. This is one of the prominent characteristics and methods of the Ba'ath Party, which it openly acknowledges in all its party literature, considering them temporary agreements imposed by current circumstances. Another evidence of the Ba'ath Party's approach is that this movement is not mentioned at all in all the original sources that dealt with contemporary political history of Iraq, except for some sources that only mentioned the name of the movement and its founder, and nothing more. These sources are detailed in the introduction.The research is divided into three sections. The first section addresses the reasons for the emergence of the organization. The second section is titled "The Program and Internal Regulations of the Arab Revolutionaries Movement - Iraq Wing." The third section explains the organizational structure of the movement. Then, the most important conclusions and the list of sources are mentioned.The research relied entirely on secret (unpublished) documents, and all documents are attached as appendices that can be seen at the end of the research